Assessing the sustainability of community livelihoods: An ecological approach to enhancing livelihoods in forest area - Supriadi; Roslinda, Emi; Hardiansyah, Gusti (Journal of Critical Ecology, 2025)
Background: This study aims to assess the level of sustainable livelihoods in a village with significant natural resource potential, analyze the assets affecting the community's livelihoods, and propose strategies to enhance sustainability. Methods: This research was conducted in Piantus Village, Sejangkung District, over four weeks, using surveys, interviews, and questionnaires. A sample of 86 families from 598 was selected through Random Sampling. Descriptive analysis, processed with Microsoft Excel, assessed five livelihood assets: human, natural, social, financial, and physical. Findings: The results of this study indicate that based on the community livelihood asset indicator index in Piantus Village, Sejangkung District, Sambas Regency, the average index scale score obtained from community livelihood assets was 0.62 with moderate criteria which means not yet sustainable. Conclusion: The strategy carried out by the Piantus Village community is the Accumulation Strategy, the condition of the assets owned by the Piantus Village community is not yet sustainable and can be said to be relatively unsustainable so that accumulation needs to be carried out to improve its condition. Novelty/Originality of This Study: By incorporating both qualitative and quantitative methods, it provides fresh insights into the challenges and opportunities for enhancing livelihood sustainability in resource-dependent communities, offering a new strategic framework for ecological-driven livelihood improvement.